How do you simplify the product (6x - 5)(3x + 1) and write it in standard form?

2 Answers
Jun 3, 2018

18x^2-9x-5

Explanation:

"each term in the second bracket is multiplied by each"
"term in the first bracket"

=(color(red)(6x-5))(3x+1)

=color(red)(6x)(3x+1)color(red)(-5)(3x+1)larrcolor(blue)"distribute"

=(color(red)(6x)xx3x)+(color(red)(6x)xx1)+(color(red)(-5)xx3x)+(color(red)(-5)xx1)

=18x^2color(blue)(+6x)color(blue)(-15x)-5larrcolor(blue)"collect like terms"

=18x^2-9x-5larrcolor(magenta)"in standard form"

Try using the FOIL method (First, Outside, Inside, Last)
18x^2-9x-5

Explanation:

You have to multiply each term in the left bracket by each term in the right bracket. The easiest way to make sure you don't miss anything is to use a systematic method such as FOIL.
The FOIL method means selecting those pairs of numbers to multiply together
Eg. (a+b)(c+d)=ac+ad+bc+bd

Question (6x-5)(3x+1)
First: 6x*3x=18x^2
Outside: 6x*1=6x
Inside:-5*3x=-15x
Last: -5*1=-5
Now we add them together
(6x-5)(3x+1)=18x^2+6x+(-15x)+(-5)
6x and -15x are like terms so they simplify
leaving us with
(6x-5)(3x+1)=18x^2-9x-5